The Syntax of relative clauses - Alexiadou, Artemis (Linguistik aktuell, 2000)
This book presents a cross-section of recent generative research into the syntax of relative clauses constructions. Most of the papers collected here react in some way to Kayne's (1994) proposal to handle relative clauses in terms of determiner complementation and raising of the relativized nominal. The editors provide a thorough introduction of these proposals, their background and motivations, arguments for and against. There are detailed studies in the syntax and the semantics of relative clauses constructions in Latin, Ancient Greek, Romanian, Hindi, (Old) English, Old High German, (dialec.